Biological Characteristics of Root Rot Pathogen on Sambucus chinensis - Ziying, Liu; Xiuling, Zhou (Plant Diseases and Pests(植物病虫害研究：英文版), 2013)
Effects of different media,pH values,temperatures,carbon and nitrogen sources on mycelial growth and sporulation of root rot pathogen on Sambucus chinensis was determined in the paper.The results showed that root rot pathogen on S.chinensis was identified as Fusariumsp.The mycelial growth and sporulation of Fusariumsp.in PSA medium was the best;the optimal temperature for mycelial growth and sporulation was from 25℃ to 30℃ and the optimal temperature was 28℃;the suitable pH values for mycelial growth and sporulation was from 5 to 7,and the optimum pH value was 6;the absence or presence of carbon sources had significant effect on growth of Fusariumsp.;sucrose was the best carbon source utilized in mycelial growth,while lactose was the worst; KNO3 was the best nitrogen source utilized in mycelial growth,while（NH4） 2 SO4 was the worst one.